Narrative engagement and entrepreneurial behaviour: A comprehensive study utilising the transportation-imagery model - Untarini, Nindria; Hartini, Sri; Rachmahani, Hera; Maulida, Intan Nia (Universitas Negeri Surabaya, Indonesia, 2024)
This study explores how narrative engagement influences story-consistent attitudes and entrepreneurial intentions among students in Indonesia. It also examines the mediating roles of enjoyment and perceived relevance in this relationship. Using Structural Equation Modelling (SEM) with Warp-PLS 8, data from 320 students who completed entrepreneurship courses were analysed. Findings reveal that narrative engagement significantly enhances enjoyment and perceived relevance, positively impacting story-consistent attitudes and entrepreneurial intentions. These results suggest that enjoyment and perceived relevance fully mediate the effects of narrative engagement, underscoring the importance of incorporating engaging and relevant narratives in entrepreneurship education to foster a stronger entrepreneurial mindset and intentions. This study offers actionable insights for educators and policymakers to design course content that maximises narrative engagement, thereby effectively shaping students' attitudes and intentions toward entrepreneurship.